A review of salt precipitation during CO2 injection into saline aquifers and its potential impact on carbon sequestration projects in China. (15th February 2023) - Cui, Guodong; Hu, Zhe; Ning, Fulong; Jiang, Shu; Wang, Rui
Graphical abstract: Salt precipitation, migration, and retention near the wellbore during CO2 injection into saline aquifers. Highlights: A critical review on salt precipitation and its influence on reservoir is presented. Salt precipitation, migration, and retention are analyzed to reveal unclear mechanism. Salt crystallization kinetics and dynamic migration are two key scientific problems. A comprehensive simulation considering all key processes needs to be performed. Salt precipitation and resolution in low-permeability saline aquifers are analyzed. Abstract: The injectivity of saline aquifers is one of the most important factors affecting CO2 geological storage. However, CO2 injection fields showed that a lot of crystallized salt precipitates out of the high-salinity water due to the water evaporation caused by dry CO2 injection, reducing the CO2 injection rate. It is still difficult to predict the distribution of precipitated salt and its effect on the porosity and permeability near the wellbore. Therefore, the process of water flow, water evaporation, salt crystallization, salt migration, and salt retention during CO2 injection into saline aquifer are reviewed in detail to analyze the key factors for accurately predicting the distribution and amount of precipitated salt. The analysis shows that the salt crystallization kinetics and precipitated salt dynamic migration are two key factors in revealing the mechanism of reservoir impairment caused by salt precipitation. To analyze salt crystallization kinetics, a lab-on-chip experiment must be developed to capture and quantify the salt crystallization under high temperature and pressure. To analyze salt dynamic migration, the CO2 flooding experiment, 3-D CT imaging, and particle flow simulation need to be analyzed to understand the dynamic migration and accumulation of precipitated salt during CO2 injection in combination. A new comprehensive simulation method that can consider these key processes is also needed to be developed to analyze the salt precipitation distribution and its influence on CO2 injectivity on a field scale. When CO2 is injected into low porosity and permeability saline aquifers in China, hydraulic fracturing can be adopted to improve injectivity, but multi-layer commingled CO2 injection should be avoided because a severe reservoir impairment caused by salt precipitation can occur even under low salinity.